Educative intervention for knowledge development on buccal health in elementary school. - Olga Lidia García Álvarez; Nora Sexto Delgado; Nereida Moya Padilla; Raúl López Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: There is high prevalence of buccal diseases which could be avoided with appropriate hygienic and alimentary habits that are supposed to be learned since the first stages of life. Objective: To verify the efficacy of an educative strategy on buccal health to develop buccal self-care through its application in girls and boys. Methods: An intervention study was developed with before and after design in 80 children of 5th grade and teachers of the primary school "Armando Mestre Martínez" in Cienfuegos, from September 2005 to March 2006. Initially, learning necessities and buccal hygiene were determined in both groups and later we verified the strategy efficiency. Initial information was obtained through surveys, focal groups, experts' opinions and observation. Wilcoxon rank test was used for matched samples and Mc Nemar test for variables verification. Findings: Significant differences were obtained between the initial and final knowledge on buccal health and buccal hygiene coefficient. Qualitative methods showed audience approval of this strategy. Conclusions: Educative strategy applications allowed children learning actions of self-care as correct teeth brushing, use of dental floss, appropriate dietary selection and identification of prejudicial habits.